2022
DOI: 10.1126/scitranslmed.abk1107
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium infantis treatment promotes weight gain in Bangladeshi infants with severe acute malnutrition

Abstract: Disrupted development of the gut microbiota is a contributing cause of childhood malnutrition. Bifidobacterium longum subspecies infantis is a prominent early colonizer of the infant gut that consumes human milk oligosaccharides (HMOs). We found that the absolute abundance of Bifidobacterium infantis is lower in 3- to 24-month-old Bangladeshi infants with severe acute malnutrition (SAM) compared to their healthy age-matched counterparts. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 70 publications
1
79
0
Order By: Relevance
“…This model explains the similarity of transcriptomic responses of B. infantis ATCC 15697 during growth in media supplemented with LNT or LNnT (39, 40) and suggests that utilization of any GlcNAc-containing glycan by this bacterium will result in upregulation of NagR-controlled genes. Among these glycans might be particular fucosylated HMOs (e.g., LNFP I) and milk N -glycans imported by different ABC transport systems (34, 73). Consistent with this notion, a previous study demonstrated that B. infantis upregulates nag and H1 cluster genes (53) when utilizing N -glycosylated human lactoferrin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This model explains the similarity of transcriptomic responses of B. infantis ATCC 15697 during growth in media supplemented with LNT or LNnT (39, 40) and suggests that utilization of any GlcNAc-containing glycan by this bacterium will result in upregulation of NagR-controlled genes. Among these glycans might be particular fucosylated HMOs (e.g., LNFP I) and milk N -glycans imported by different ABC transport systems (34, 73). Consistent with this notion, a previous study demonstrated that B. infantis upregulates nag and H1 cluster genes (53) when utilizing N -glycosylated human lactoferrin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, different GlcNAc derivatives serve as effector molecules of these TFs: GlcNAc for NahR and GlcNAc-6S for AtsR (44, 59). Another NagR paralog in B. infantis 2D9, NglR, potentially controls a genomic locus involved in utilizing complex N -glycans (73) ( Table 2 ). Overall, these observations illustrate how bifidobacteria adapted to regulate the foraging of host glycans during colonization of mammalian hosts and shed more light on how complex regulatory networks emerge and evolve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the complementary synbiotics described above for reducing sepsis and modulating microbiome composition in infants, other potentially synergistic synbiotics have also been developed using B. infantis. In a recent report (Barratt et al, 2022), infants with acute malnutrition were given B. infantis with or without HMO lacto-N-neotetraose. Although both treatments led to engraftment of the B. infantis strain and promoted weight gain in the infants, the synbiotic did not enhance the effect compared to the B. infantis-only treatment.…”
Section: Recent Examplesmentioning
confidence: 99%